Análise da correlação entre os indicadores de exploração e produção e a criação de valor econômico: um estudo aplicado às empresas integradas do setor petrolífero mundial - Machado, Julio Henrique (2010)
The oil is an essential commodity to the modern economy and it will continue being at least during the first half of 21st century. The fact of the remaining reserves are in deep and ultradeep waters, makes the sector demands considerable investments in research, extration and production. Thus, the petroliferous ones need to have a satisfactory performance, remunerating the shareholders of this sector. In this context, the research is developed with the general objective to analyze the capacity of the companies of the petroliferous sector, in creating economic value and keeping them consistent in the long stated period. For the reach of the general objective, the specific objective is to describe the characteristics of this sector as well as the theoretical referencial being involved theories of the capital structure and value based management. The sample is composed by 10 integrated company of oil listed in the New York Stock Exchange - NYSE. For the correlation study, the activities of exploration and production (E&P) called independent and the economic value added (EVA) called dependent. It has observed that there is not a trend of correlation in the companies, therefore was influenced by the price of market of the barrel and also by the premium demanded for the risk, that varied in the years in analysis. One notices that the reserves are in decline, due to difficulty in its replacement, what it represents uncertainty about the generation of economic value in this sector considering the long stated period